Development of Polymorphic Microsatellites in White Scar Oyster Crassostrea belcheri - Nirandon Phuwan (Science Faculty of Chiang Mai University, 2019)
The white scar oyster Crassostrea belcheri is one of economically important species in Thailand. To improve the management efficiency of C. belcheri, appropriate molecular markers are needed to be developed. In this study, microsatellites in C. belcheri were cross-amplified using type I microsatellites designed from express sequence tag (EST) of Crassostrea gigas. In total, 60 EST-derived microsatellites of C. gigas were tested and 41 loci (68.33%) generated the amplification product against genomic DNA of C. belcheri. Of these, 18 loci (43.90%) were polymorphic and were preliminary screened for estimation of a polymorphic level against C. belcheri originating from Surat Thani (N = 50). The number of alleles per locus ranged from 4 to 15 with an average number of 8.83 alleles per locus. The observed heterozygosity varied from 0.0000 to 0.8571 with an average of 0.3982 whereas the expected heterozygosity ranged from 0.4149 to 0.8930 with an average of 0.7487. These polymorphic microsatellites were further tested against bulked genomic DNA (5 bulks with 10 individuals for each bulk) from 5 different geographic locations. Thirteen pairs of primers generated the positive amplification products across all examined geographic samples while two pairs of primers yielded the amplification products only in the Surat Thani sample and they were regarded as candidate population-specific markers. Microsatellites in the present study provide a valuable fundamental resource to facilitate further research on population genetics and stock management of C. belcheri in Thailand.